2014
DOI: 10.14804/1-1-26
|View full text |Cite
|
Sign up to set email alerts
|

The Current Status of the Education and Training of Nurse Educators in South Africa

Abstract: Human resource for health is a global concern, with a shortage of doctors, nurses and midwives to meet the Millennium Development Goals. Nurses form the bulk of the healthcare workforce and are found to service remote areas where doctors are not available. The World Health Assembly in recognition of the human resource crisis passed resolutions for strengthening nursing and midwifery services. Nationally, the Forum for University Nursing Deans in South Africa (FUNDISA) realized that it was impossible to respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…It was evident that NNEs learned a lot about their novel profession through these workshops and conferences but these workshops were on broad topics and not based on the individual needs of participants. These findings corroborate existing scholarly studies (Mulaudzi et al, 2014; Owens, 2018; Shapiro, 2018). This finding is not different from a phenomenological study in Iran where Iranian novice faculty members had to attend a set of educational workshops on teaching and assessment methods to facilitate their transition process (Heydari et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It was evident that NNEs learned a lot about their novel profession through these workshops and conferences but these workshops were on broad topics and not based on the individual needs of participants. These findings corroborate existing scholarly studies (Mulaudzi et al, 2014; Owens, 2018; Shapiro, 2018). This finding is not different from a phenomenological study in Iran where Iranian novice faculty members had to attend a set of educational workshops on teaching and assessment methods to facilitate their transition process (Heydari et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Studies on the facilitators of the transition from practice to academia are limited in Africa (Mulaudzi et al, 2014). For instance, a South African study involving neophyte nurse educators revealed that attending conferences and in-service training, and formal mentorship was the most common assistance offered to South African neophytes nurse educators (Mulaudzi et al, 2014). Also, through a qualitative and theory-generating study, a model for mentoring newly appointed nurse educators in nursing education institutions in South Africa was developed and has been a major facilitator of the transition from practice to academia in South Africa (Seekoe, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the nursing education institution and, specifically, the nurse educator, has developed and become more complex as higher education and the science of nursing developed (Blaauw et al 2014a). Globally, there is a pressing need for skilled nursing professionals (Mulaudzi et al 2012;World Health Organization (WHO) 2016;Vierula et al 2020;Chinembiri 2017). In this regard, the nurse educator is an important role player in shaping the quality of the programme to ensure the preparation of competent professionals (Billings et al 2019; WHO 2016).…”
Section: The Responsibility Of the Nurse Educator In Higher Educationmentioning
confidence: 99%
“…PEPFAR through the Nursing Education Partnership Initiative (NEPI) and the World Health Organisation launched a major initiative for the up-scaling of transformative nursing education in Africa during 2010. Mulaudzi, Daniels, Direko, and Uys (2012) is of the opinion that not only should the quantity of health professionals increase but the quality of the professionals must be addressed.…”
Section: Literature Reviewmentioning
confidence: 99%